2023
DOI: 10.1038/s41427-022-00460-x
|View full text |Cite
|
Sign up to set email alerts
|

Interface engineering for substantial performance enhancement in epitaxial all-perovskite oxide capacitors

Abstract: Capacitors based on ABO3-type perovskite oxides show considerable promise for overcoming the limitations of nanoscale integration with dynamic random access memory (DRAM) devices. Among the thermodynamically stable perovskite oxides, titanates (ATiO3) exhibit high dielectric permittivity in metal–insulator–metal (MIM) configurations. However, their performance in mitigating the large leakage current caused by their narrow bandgap (3 eV) remain under scrutiny. Herein, substantially enhanced dielectric propertie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…If Ru diffuses from the bottom SrRuO 3 electrode to the Ba 0.5 Sr 0.5 TiO 3 dielectric, the diffused Ru can form shallow‐level defects of 0.07–0.12 eV and act as a trap site for P‐F emission. [ 17 ] Both capacitors in this study demonstrated P‐F emissions with trap sites that have an energy level of 0.1 eV; thus, this P‐F emission can be attributed to Ru diffusion from the bottom electrode. Meanwhile, the dominant conduction mechanism of the capacitor with the Ru top electrode changed from the P‐F emission to the hopping conduction in the high voltage area, unlike the capacitor with the SrRuO 3 top electrode.…”
Section: Resultsmentioning
confidence: 82%
“…If Ru diffuses from the bottom SrRuO 3 electrode to the Ba 0.5 Sr 0.5 TiO 3 dielectric, the diffused Ru can form shallow‐level defects of 0.07–0.12 eV and act as a trap site for P‐F emission. [ 17 ] Both capacitors in this study demonstrated P‐F emissions with trap sites that have an energy level of 0.1 eV; thus, this P‐F emission can be attributed to Ru diffusion from the bottom electrode. Meanwhile, the dominant conduction mechanism of the capacitor with the Ru top electrode changed from the P‐F emission to the hopping conduction in the high voltage area, unlike the capacitor with the SrRuO 3 top electrode.…”
Section: Resultsmentioning
confidence: 82%
“…The possibility for groundbreaking research lies at the interface of robust perovskite systems, where control of spin, charge, orbital, and lattice interactions holds immense possibilities from both fundamental and device perspectives. 1,2,3 To unravel the correlations among these diverse degrees of freedom, numerous approaches are being studied, including engineering of strain 4,5 , interface 6 , defects 7,8 and symmetry. 9,10 However, scant attention has been paid to the engineering of bonding geometry within and in-between metal-oxygen octahedra.…”
mentioning
confidence: 99%
“…24 However, their effectiveness is constrained by the demand for high-quality interfaces. Interestingly, the unstrained perovskite LaCoO3 (LCO) is merely an insulator and non-magnetic (paramagnetic) material that exhibits a systematic temperaturedependent spin-state transition starting from a low spin state (LS, t2g 6 , S = 0) to an intermediate spin state (IS, t2g 5 eg 1 , S = 1) or a high spin state (HS, t2g 4 eg 2 , S = 2). 25,26,27 Nevertheless, the single layer LCO thin films can exhibit unusual ferromagnetic insulator (FMI) behavior with Curie temperature (TC) ranging from 24-92 K, depending on the substrate-induced strain.…”
mentioning
confidence: 99%